Early post-embryonic development in Ellipsostrenua (Trilobita, Cambrian, Sweden) and the developmental patterns in Ellipsocephaloidea. (18th June 2018) - Laibl, Lukáš; Cederström, Peter; Ahlberg, Per
Abstract: This study documents the early post-embryonic developmental stages (protaspides and early meraspides) of the Cambrian trilobite Ellipsostrenua granulosa (Ahlberg, 1984) from the Gärdsjön Formation of Jämtland, Sweden. The early protaspid stage is characterized by a circular outline of the exoskeleton, two pairs of fixigenal spines, a short preglabellar field, a genal swelling, and prominent bacullae. The late protaspid stage differs only in having the trunk portion discernible. Early meraspid cranidia are sub-rectangular with prominent palpebral lobes, a wide anterior margin, a proportionally long anterior branch of the facial suture, and intergenal spines. Meraspid pygidia tentatively assigned to this species possess comparatively long macrospines. Small hypostomes associated with E . granulosa bear at least four pairs of marginal spines. A comparison of the early developmental stages of E . granulosa with some other species of Ellipsocephalidae and with species of the closely related Estaingiidae reveals several similarities. The conservative morphology of the early protaspid stage with only two pairs of fixigenal spines, the timing of the development of the trunk portion, and the presence of genal swellings and prominent bacullae could be phylogenetically informative. The range of size variation of the early protaspid stages in two families may be related either to taxonomical differences between Ellipsocephalidae and Estaingiidae, or to environmental differences in various paleogeographic settings.